Fighting Against Agoraphobia in the Highly Illogical Novel Behaviour by John Corey Whaley (2016) - Hasan, Abel; Anwar, Desvalini (Universitas Negeri Padang, 2023)
This research purpose is to describe the main character experiences of suffering from agoraphobia, type of anxiety disorder in the novel Highly Illogical Behavior by John Corey Whaley. The psychoanalysis behaviorism theory by John B Watson is used to determine the stimuli and responses that result in changes of the behaviors of the main character. The analysis of the novel also shows the symptoms that occur in the characters and what the efforts of the characters in the novel are to cure or overcome agoraphobia. Through a careful examination of the narrative, character dynamics, and key scenes, this analysis identifies the stimuli that elicit agoraphobic responses in the protagonist, Solomon Reed. It investigates the specific environmental and social factors that serve as triggers for Solomon's anxiety and subsequent avoidance behavior. These stimuli include crowded spaces, unfamiliar settings, and social interactions that have previously caused distress or panic attacks for Solomon. Furthermore, this analysis scrutinizes Solomon's responses to these stimuli, focusing on his avoidance behavior and the measures he takes to control his anxiety. It delves into his meticulous routines, the establishment of safe spaces within his home, and the development of coping mechanisms that allow him to navigate his daily life within the confines of his own environment. The result of this study is that the main character can overcome the agoraphobia he suffers with the help of the environment such as family and friends.